Application of Biochar Derived From Pyrolysis of Waste Fiberboard on Tetracycline Adsorption in Aqueous Solution - Xu, Deliang; Gao, Yaxuan; Lin, Zixiang; Gao, Wenran; Zhang, Hong; Karnowo, Karnowo; Hu, Xun; Sun, Hongqi; Syed-Hassan, Syed Shatir A.; Zhang, Shu (Frontiers in Chemistry, 2020)
In this study, biochars derived from waste fiberboard biomass were applied in tetracycline (TC) removal in aqueous solution. Biochar samples were prepared by slow pyrolysis at 300 ℃, 500 ℃, and 800 ℃, and were characterized by ultimate analysis, Fourier transform infrared (FTIR), Scan-ning electron microscopy (SEM), X-ray photoelectron spectroscopy(XPS), Brunau-er-Emmett-Teller (BET) etc. The effects of ionic strength (0–1.0 mol/L of NaCl), initial TC con-centration (2.5–60 ppm), biochar dosage (1.5–2.5 g/L), and initial pH (2–10) were systemically determined. The results present that biochar prepared at 800 ℃ (BC800) generally possesses the highest aromatization degree and surface area with abundant pyridinic N (N-6), and accordingly shows a better removal efficiency (68.6%) than the other two biochar samples. Adsorption iso-therm data were better fitted by the Freundlich model (R2 is 0.94) than the Langmuir model (R2 is 0.85). Thermodynamic study showed the adsorption process is endothermic and mainly physical in nature with the values of ΔH0 being 48.0 KJ/mol, ΔS0 being 157.1 J/mol/K, and ΔG0 varying from 1.02 to -2.14 KJ/mol. The graphite-like structure in biochar enables the π-π interactions with ring structure in TC molecule which together with the N-6 acting as electron donor is the main driven force of adsorption process.